2005
DOI: 10.1097/01.blo.0000176148.39380.ff
|View full text |Cite
|
Sign up to set email alerts
|

Bone Strength Influences Periprosthetic Bone Loss after Hip Arthroplasty

Abstract: Prognostic Study, Level I (high quality prospective study-all patients were enrolled at the same point in their disease with > or = 80% followup of enrolled patients). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Patients in the placebo group with low pre-operative bone mass had lost 23% and 27% in zones 1 and 7 of the operated hip after 2 years, whereas patients with high systemic BMD lost only 14% and 11% respectively. This is consistent with results from earlier studies showing a correlation between low preoperative bone mass and increased bone loss around uncemented stems (33,220). Another factor influencing periprosthetic BMD was the stem diameter.…”
Section: Periprosthetic Bone Mineral Changessupporting
confidence: 91%
“…Patients in the placebo group with low pre-operative bone mass had lost 23% and 27% in zones 1 and 7 of the operated hip after 2 years, whereas patients with high systemic BMD lost only 14% and 11% respectively. This is consistent with results from earlier studies showing a correlation between low preoperative bone mass and increased bone loss around uncemented stems (33,220). Another factor influencing periprosthetic BMD was the stem diameter.…”
Section: Periprosthetic Bone Mineral Changessupporting
confidence: 91%
“…6,50 The greatest change tends to be in the proximal zones with a wide spread of results in zone 1. 7,8,12,40,41,[47][48][49]51 Nivbrant et al, 49 comparing the Lubinus SPII with an SHP prosthesis, found a 9% loss for the former and 1% in the latter in zone 1, with a reported range of results in this study from À31 to þ40% in the Lubinus and À19 to þ17% in the SHP. Grant 41 reported a similarly wide range of results (À5 to þ37%) in a DXA study of the elite stem.…”
Section: Discussionmentioning
confidence: 72%
“…16,39 Its potential effects on THA studies have rarely been acknowledged. Arabmotlagh 40 suggested that preservation of BMD in zone 1 of some of their study group might have been due to the effects of HO, and a recent study examining femoral remodeling excluded a patient with ''extensive'' HO from analysis. 41 However, our study shows that merely excluding ''extensive'' HO is insufficient, as even mild HO produces a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…We used a multiple linear regression analysis to analyze which factors influenced bone loss in the entire periprosthetic region at 4 years. Factors separately investigated in the analysis was exposure (OA vs. fracture) and covariates who, from other studies, are known to influence bone remodeling around implants (preoperative bone mineral density in the hip, sex, age, body mass index, and stem size) . Pearsońs Chi‐squared test was used to compare the categorical variables between the groups.…”
Section: Methodsmentioning
confidence: 99%